Analisis Kesalahan Berbahasa Pada Presentasi Mahasiswa Prodi Pendidikan Bahasa Indonesia - Ruth Astrinata Sihite; Marlina Elisa Marpaung; Kirana Pranata S. Brahmana; Elisa Raskin Br Pinem; Ewis Sinaga; Lasenna Siallagan (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Language errors are inappropriate or incorrect use of grammar rules, vocabulary, spelling, or sentence structure in a language. Language errors can occur due to various factors, such as a lack of understanding of grammatical rules, influence from other languages, or lack of awareness of correct and appropriate usage in certain communication situations. This research aims to analyze errors in using Indonesian properly in making presentations by students of the Indonesian Language Education Study Program at Medan State University. The method used for research and collecting data is through direct observation through presentations during lectures via Via-zoom media by recording the progress of the presentation. The implication of this research is the importance of increasing understanding and mastery of good and standard Indonesian for students. The research target is students of the Class C Indonesian language study program class of 2022 at Medan State University in order to improve the quality of presentations for the future. Keywords:, ,